The impact of supply chain integration on improving operations performance in construction companies (A field study on civil construction companies in Lattakia Governorate) - أحمد تميم; محمد رامي; ناصر سومر (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The research aims to identify the types of supply chain integration, and the research also aims to show the impact of supply chain integration in its various forms (internal integration, external integration, strategic integration) in improving the performance of operations in its dimensions (improving quality, reducing cost, increasing flexibility, reducing delivery time ). The researcher followed the descriptive analytical approach, where the researcher touched on the concept of the supply chain, its importance, and success factors, in the theoretical framework, and the concept of supply chain integration, and forms of supply chain integration, and the concept of operations performance, its importance and dimensions of performance were also addressed. Operations, as for the practical framework, a questionnaire was designed and distributed to the research sample, which has a size of (78) individuals. The data was analyzed using the (SPSS23) program in order to reach the required results. The study reached several results, the most important of which is the presence of a significant effect of supply chain integration on the performance of operations in the construction companies under study, where there is a positive correlation between supply chain integration and operations performance, where the Pearson correlation coefficient between the two main variables of the study was (0.817), and this indicates that There is a high correlation between the two variables.